Identification of Mineral Zircon (ZrSiO4) Rare Earth Metal (REM) As Smart Material For Electric Tactical Motor Bike Battery - Dimas Prayogo; Riri Murniati; Chutiwat Likitaporn (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2024)
Rare earth metals are associated minerals that are magnetic used as the main component in providing power to most electronic devices. Rare earth metal (REM) as a smart material that has 14 chemical elements. These elements are grouped according to their molecular weight, namely light rare earth metals (Ce, Pr, Nd, Pm, Sm, Eu) and heavy rare earth metals (Gd, Tb, Dy, Ho, Tr, Tm, Yb, Lu) . The use of this REM includes electric cars, health identification devices, LCDs and computer hardware. From some of the benefits and contents of REM, its development is not only in the industrial world but also in the world of defense, one of which is as a battery for motorized vehicles developed by the ministry of defense (Electric Tactical Motor Bike) that uses lithium batteries as a source of electrical energy. However, the use of lithium batteries which have shortcomings in terms of charging makes them look for other alternatives so that they can be charged optimally, one of which is using REM. The strategic position of rare earth minerals in the future must be developed so that they can be used sustainably, considering that Indonesia has potential resources that can be utilized.